Impact investigation of turbulence image features on the computation of flow kinetic energy. (1st January 2012) - Liang, Zhongwei; Tao, Jianhua; Liu, Xiaochu; Deng, Wu
For the purpose of obtaining the accurate characteristics of turbulence motion locus in strengthen grinding, we quantitative studied the influence of image features on selecting fluid models when computing flow kinetic energy and its spatial distribution simulation. Through the turbulence image signal is sampled in a grinding flow field, we realised the multi-precision expression of image signal group for quantifying its mathematical characteristics, then established typical fluid models and deduced the computing formulas for kinetic energy. In an experiment, we use turbulence from strengthen grinding as an example, with fuzzy relational degree and central-limit variance were used for analysing and comparing the variation tendencies of those obtained kinetic energy. Finally, the computer simulation of kinetic energy spatial distribution is realised in Fluent 6.2.23, which helps to establish the influence mechanism and mutual relationship between turbulence image features and the computation of flow kinetic energy, the technical reference for turbulence monitoring can be provided.